Multimodal characterization of the bone-implant interface using Raman spectroscopy and nanoindentation. (October 2020) - Fraulob, Manon; Pang, Siyuan; Le Cann, Sophie; Vayron, Romain; Laurent-Brocq, Mathilde; Todatry, Soorya; Soares, Julio A.N.T.; Jasiuk, Iwona; Haïat, Guillaume
Highlights: Standardized in vivo implant model well-adapted to study the bone-implant interface. Bimodal complementary nanoscale compositional and microscale elastic measurements. Lower mineralization and elastic properties attest of immature newly formed bone. Abstract: Titanium implants are widely used in dental and orthopedic surgeries. Osseointegration phenomena lead to direct contact between bone tissue and the implant surface. The quality of the bone-implant interface (BII), resulting from the properties of newly formed bone, determines the implant stability. This study investigates the BII properties using a dedicated in vivo implant model consisting of a coin-shaped Ti-6Al-4V implant inserted in a rabbit femur for 10 weeks. A gap created below the implant was filled with newly formed bone tissue after healing. The properties of mature and newly formed bone tissues were compared using: i) Raman spectroscopy to assess the nanoscale compositional bone properties and ii) nanoindentation to quantify microscale elastic properties in site-matched regions. The mineral-to-matrix ratio, crystallinity (mineral size and lattice order), and the collagen cross-link ratio were significantly lower in newly formed bone tissue (e.g., a mineral-to-matrix ratio of 9.3 ± 0.5 for proline 853 cm −1 ) compared to mature bone (15.6 ± 1). Nanoindentation measurements gave Young's modulus of 12.8 ± 1.8 GPa for newly formed bone and 15.7 ± 2.3 GPa for mature bone. This multimodal and multiscale approach leads to a better understanding of osseointegration phenomena.